Improving the yield of a solar still with the aid of an evacuated tube. Issue 1 (1st July 2022) - Mohammad Akram, CH.; Saritha, G.; Sharma, Arvind; Singh, Hari Kumar; Rinawa, Moti Lal; Ashwin Kannan, S.
Abstract: Solar distilling process is a viable way to supplying clean freshwater to remote populations with low water condition and sufficient sunshine. Because, water purified in a simple solar still yields less, and hence, it would not be widely utilized or traded. The effectiveness of a traditional solar still is highly dependent on the quantity of energy received by the solar still's bottom surface. Thus, expanding either the absorption capacity of the basin surface or the rate of energy transfer to the saline water would then result in an enhancement in potable water yield levels. Through the coupling of an evacuated glass tube (EGT), an effort has been made to increase the evaporative heat transfer and solar still heat transfer effectiveness in this study. Further, the current research analysis compares the performance of the ordinary (Plain-Still) and evacuated tube linked solar stills (EGT-Still) at a fixed water level of 2.0 cm. The findings demonstrated that integrating an evacuated tube with the traditional solar still increased the solar still's productivity by 13.73%.